Rapid Evaluation of All-Optical Modulation in Quantum Cascade Laser Using Photoluminescence Spectrum - Haijun Zhou; Chen Peng; Liguo Zhu; Tao Chen; Yuankun Sun; Gang Chen; Zeren Li; Qixian Peng; Peng Feng; Biao Wei (IEEE Photonics Journal)
All-optical modulation in a quantum cascade laser (QCL) can be rapidly evaluated using a photoluminescence (PL) spectrum. The PL spectrum reflects the electron transition rate of the sub-bands of the active region of a QCL. The peak position, amplitude, and displacement of the PL spectrum can be used to determine the optimal wavelength, spot position, the laser incident angle, optical power, and displacement in the electric field of the near-infrared laser. This PL spectrum approach is rapid, accurate, and simple. Furthermore, it can be used to optimize high-speed all-optical modulation of QCLs for use in free-space optical communication and molecular-detection applications.